Forças armadas na segurança interna - Macie, Albano (2019)
The present thesis, entitled "Armed Forces in Homeland Security: The case of Mozambique", analyzes the assumptions of intervention of the FAs in the IS, the proper field of action of the police forces, in a Mozambican conjuncture, where the military institution is ―suis generis‖, resulting from: (i) the birth of the FAs in the circumstance of the African struggles for independence; (ii) the transformation of guerrilla forces into state FAs in 1975, with the proclamation of independence and its consolidation in the context of the single Party that governs the State and Society; (iii) the dismantling of these FAs, in 1992, as a result of the PGA, to constitute a new institution, according to the principle of parity between government forces (led by FRELIMO) and forces from RENAMO (belligerent guerrilla movement), where each party indicated 50% of the workforce. Based on the concept of prevailing national defense and the political reality underlying it, two theses arise: (i) FAs should collaborate in the implementation of defense policy, but they can not be, in the current scenario of pacification of the country, the priority instrument for IS, so that they are not used to overcome internal political crises and reduce the scope of political opponents of PR and its Party; (ii) de iure condendo, from the concept of national defense adopted, the intermediate, the FAs can act in the IS, not only in exceptional cases (states of siege and emergency), but also in a subsidiary way, when the capabilities of the forces (border) in the face of the current overlap between external and internal threats and increasing organized and violent crime, and in a complementary way to carry out civil protection, reconstruction and national development activities.